High Loss to Followup and Early Mortality Create Substantial Reduction in Patient Retention at Antiretroviral Treatment Program in North-West Ethiopia - Wubshet, Mamo (International Scholarly Research Network, 2012)
Background. There has been a rapid scale up of antiretroviral therapy (ART) in Ethiopia since 2005. We aimed to evaluate mortality, loss to followup, and retention in care at HIV Clinic, University of Gondar Hospital, north-west Ethiopia. Method. A retrospective patient chart record analysis was performed on adult AIDS patients enrolled in the treatment program starting from 1 March 2005. We performed survival analysis to determine, mortality, loss to followup and retention in care. Results. A total of 3012 AIDS patients were enrolled in the ART Program between March 2005 and August 2010. At the end of the 66 months of the program initiation, 61.4% of the patients were retained on treatment, 10.4% died, and 31.4% were lost to followup. Fifty-six percent of the deaths and 46% of those lost to followup occurred in the first year of treatment. Male gender (adjusted hazard ratio (AHR) was 3.26; 95% CI: 2.19–4.88); CD4 count ≤200 cells/μL (AHR 5.02; 95% CI: 2.03–12.39), tuberculosis (AHR 2.91; 95% CI: 2.11–4.02); bed-ridden functional status (AHR 12.88; 95% CI: 8.19–20.26) were predictors of mortality, whereas only CD4 count <200 cells/μL (HR = 1.33; 95% CI: (0.95, 1.88) and ambulatory functional status (HR = 1.65; 95% CI: (1.22, 2.23) were significantly associated with LTF. Conclusion. Loss to followup and mortality in the first year following enrollment remain a challenge for retention of patients in care. Strengthening patient monitoring can improve patient retention AIDS care.